EFEKTIVITAS ORGANISASI BADAN PERMUSYAWARATAN DESA DALAM PENYUSUNAN DAN PENETAPAN PERATURAN DESA: Studi Di Desa Mautenda, Kecamatan Wewaria, Kabupaten Ende, Provinsi Nusa Tenggara Timur - Alie Zainal Abidin; Taufiq Soeltanto; Marianus Ne’e (JOURNAL AKSES STIA MALANG, 2023)
The village is the smallest government of the Unitary State of the Republic of Indonesia, in carrying out its dutiesthe village needs an institution, namely the Village Consultative Body (BPD). The Village Consultative Body(BPD) is a form of democracy at the Village Autonomy level. The Village Consultative Body (BPD) functions todetermine village regulations with the village head, accommodate and channel the aspirations of the community,therefore the Village Consultative Body (BPD) as a consultative body originating from the village community, inaddition to carrying out its function as a bridge connecting the village head with the village community, must alsocarry out its main function, namely the function of representation (representation). The purpose of this researcheris to find out about the Organizational Effectiveness of Village Consultative Bodies (BPD) in the Preparation andDetermination of Village Regulations in Mautenda Village, Wewaria District, Ende Regency, East NusaTenggara. The benefits of this study are to determine the influencing factors in the Process of Implementing thePreparation and Determination of Village Regulations in Mautenda Village, Wewaria District, Ende Regency,East Nusa Tenggara. Effectiveness is how well the work is done and the extent to which people produce somethingas expected. This means that if a job can be completed according to planning both in terms of time, cost andquality, it can be said to be effective. This is so that the Village Consultative Body (BPD) in carrying out the task of achieving directed targets and organizational goals can be achieved. So researchers describe it in the form ofdata using Qualitative Research Methods with a descriptive approach, through data collection techniques such asobservation, interviews and documentation with the aim of parsing in detail. Based on the results of research inMautenda Village, Ende Regency, East Nusa Tenggara regarding the Effectiveness of Village Consultative Body(BPD) Organizations in the Preparation and Determination of Village Regulations has been very effective Inaccordance with article 30 of the Regional Regulation of Ende Regency Number 8 of 2017 concerning thefunctions, duties and authorities of the Village Consultative Body which functions to discuss and agree on theDraft Village Regulation with the village head, Accommodating and channeling the aspirations of the villagecommunity and also supervising the performance of the village head.